MODERN TOOLS OF THE SYSTEM ANALYSIS OF POLITICAL REFORMS IN RUSSIA - V. P. Miletsky; K. B. Dorogoij (Дискурс, 2017)
The heuristic potential of discourse analysis and content analysis in study of political reformation in Russia is considered. The attention is drawn to methodological problems, which appear in the process of systemic social research of systemic political processes. The content analysis of the Addresses of the President of the Russian Federation shows correlation between discussion about reformation and actual course of reform. In this connection understanding of the text as a social reality is substantiated and actuality of discourse analysis and content analysis of political realm increases.